2016
DOI: 10.1136/ejhpharm-2016-001067
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal cyclodextrin in the treatment of Niemann-Pick disease type C

Abstract: CaseA child with Niemann-Pick disease type C was started on miglustat therapy at the age of 2 years. Intrathecal administration of hydroxypropyl-β-cyclodextrin was added 5 months later. The initial dose of 175 mg was gradually increased over the first 6 months to reach 325 mg. The drug was administered every 15 days, and the patient received 43 doses. A slight delay in progression of the disease was seen during the first year of intrathecal hydroxypropyl-β-cyclodextrin. However, additional symptoms have emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Brain imaging in NPC is usually nonspecific early in the disease and is often reported as cerebellar and cerebral atrophy at later stages of progression. In the EIF cohort reviewed here we found that brain atrophy and white matter signal abnormalities were the most frequent changes reported [ 42 , 49 , 50 , 51 ] consistent with other studies [ 82 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Brain imaging in NPC is usually nonspecific early in the disease and is often reported as cerebellar and cerebral atrophy at later stages of progression. In the EIF cohort reviewed here we found that brain atrophy and white matter signal abnormalities were the most frequent changes reported [ 42 , 49 , 50 , 51 ] consistent with other studies [ 82 ].…”
Section: Discussionsupporting
confidence: 91%
“…Neuroimaging data was available in 10/81 patients and only one of them was reported as normal [ 51 ]. Cerebral atrophy was mentioned in nine patients [ 42 , 46 , 49 , 50 ]. Deep white matter signal abnormalities were seen in six patients [ 42 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has proposed hydroxypropyl-β-cyclodextrin (HPβCD) as a new line of treatment for NPC disease, as it could minimize neurological damage, reduce symptoms, and delay progression [ 97 , 98 ]. The therapeutic efficacy of HPβCD was discovered casually, following its use as an excipient to administer allopregnanolone in an NPC1 mouse model [ 99 ].…”
Section: Therapeutic Approaches Used To Counteract Cognitive Deficitsmentioning
confidence: 99%
“…The most relevant toxicities were intermittent fever and a suspicion of chemical meningitis [32,46]. A recently published article described the IT therapy of a young NPD-C girl of 22 months [47]. The dosage of HP-β-CD was 175-325 mg every 2 weeks for 20 months.…”
Section: Experience In Humans: Efficacy Of the Intrathecal Administramentioning
confidence: 99%